sports game to develop speed with middle school students - bektache, bahia; selami, sid ali (sports creativity, 2025)
This study aims to determine the extent to which semi-sports contribute to the development of the character of speed in middle-class students (11-13) years, where the researchers used the experimental method and may be a community study of 600 students from the middle of Ras Souta, State of Algeria, and the sample of the study was 40 pupils (male and female) selected in a deliberate way due to the nature of the research, the researchers used an educational program consisting of a set of classes to measure the development of the capacity of the speed as a study tool and the study test was used as a statistical tool to analyze and interpret the results. The study concluded that a significant improvement in the development of the character of speed in middle school students through the application of the semi-sports program, and came up with recommendations, the most important of which were: guided by the scientific foundations in the construction of an educational unit in sports semi-sports in accordance with the content of the article curriculum for the development of physical abilities